Enhancing Biotechnology Literacy through Kombucha Tea Making Socialization at SMA Negeri 1 Giri - Istiqomah Rahmawati; Bekti Palupi; Merymistika Yufrani Afred; Agus Wedi Pratama (Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
Biotechnology learning at the secondary school level is often dominated by theoretical approaches, potentially limiting students' understanding of real-life scientific applications. This community service activity aimed to implement the Tri Dharma of Higher Education through socialization and training on kombucha tea making at SMA Negeri 1 Giri, Banyuwangi. The primary objective of this program was to strengthen students' applied biotechnology literacy and foster an entrepreneurial spirit by introducing the business potential of fermented products. The implementation method employed a participatory approach involving 53 students as active participants on March 18, 2025. The activity stages included interactive material delivery regarding SCOBY (Symbiotic Culture of Bacteria and Yeast) microbiology and the health benefits of kombucha, followed by practical demonstrations covering the process from starter inoculation to fermentation. In addition to technical aspects, this activity specifically incorporated training on simple economic analysis, including calculations for raw material costs, production expenses, and the determination of competitive selling prices for a home-industry scale. The results indicated high participant enthusiasm, evidenced by active participation in discussion and quiz sessions. Students successfully gained a deep understanding of the biochemical reactions occurring during fermentation and the potential of kombucha as a functional beverage. Furthermore, the provided business insights transformed students' perspectives, highlighting the high economic value of biotechnology products. It is concluded that the integration of practical training and business insights effectively enhances students' scientific competence while supporting the implementation of the entrepreneurship theme within the Merdeka Curriculum.